Legal Recognition of Business Incubators: Ethics, Compliance, and Corruption Prevention in Strengthening MSMEs - Lyna Latifah; Isti Hidayah; Fafurida; Budi Prasetiyo; Barokah Isdaryanti (Universitas Negeri Semarang, 2025)
This study examines the absence of explicit legal regulation for business incubators in Indonesia and its implications for their role in supporting MSMEs and startups. Business incubators play an important role in inclusive economic development through mentoring services, business networking, and financing facilitation. Yet, they lack legal personhood and generally operate under parent institutions such as universities or government agencies, creating operational limitations and potential corruption risks. This research uses a normative and comparative juridical approach. Analysis is conducted on national laws and regulations and comparative studies on policies in other countries, such as South Korea, Singapore, and Malaysia. The key finding is that despite various policies supporting entrepreneurship, no regulation directly recognizes incubators as independent legal entities. Data were obtained through documentary and literature studies, then analyzed qualitatively through systematic, prescriptive, and comparative approaches. The results show that while several regulations support entrepreneurship development, none provide explicit legal recognition of incubators as independent legal subjects. Incubators generally operate under parent institutions such as universities or government agencies, which limits contractual flexibility and access to funding sources. This research, therefore, recommends the formulation of specific regulations or standardized governance mechanisms to ensure legal certainty, institutional accountability, and long-term sustainability. As a result, the operational effectiveness and sustainability of incubators are improved. Such reforms are expected to provide legal certainty, strengthen institutional accountability, and encourage the strengthening of the national innovation and entrepreneurship ecosystem. Clear legal recognition would enable incubators to function more effectively as innovation and MSME growth catalysts.